CONSERVATION OF GENETIC DIVERSITY WITHIN AND AMONG SUBSPECIES OF WILD TURKEY - Karen E. Mock; Tad C. Theimer; David L. Greenberg; Paul Keim (Wildlife Society Bulletin)
Abstract: Genetic differences among 5 subspecies of wild turkey (Meleagris gallopavo) were assessed using amplified fragment length polymorphism (AFLP) analysis. DNA marker profiles were obtained for 358 birds, representing a total of 24 populations across North America. Highly significant differences in marker frequencies were found between all pairs of subspecies (P < 0.0001) except the eastern (M. g. silvestris) and Florida (M. g. osceola) subspecies (P = 0.046). Genetic distances between pairs of populations were also consistently smaller within subspecies than between subspecies, with the exception of the eastern and Florida subspecies. The Gould's subspecies (M. g. mexicana) was found to be the most genetically divergent. We recommend that the genetic structure at both the subspecies and population levels be considered when making decisions about translocations and the management of mixed‐subspecies populations.